Use cases and personas: uses in service sector simulation development. (10th March 2009) - McHaney, Roger W.
Use cases and personas are systems design tools applied to user interface creation for representing human behaviour. This paper moves these tools to simulation design, where human factors are a key component. This paper presents examples showing how personas and use cases are complementary in interface design then demonstrates how the same tools can be adapted to specify actions of human interaction with system components within the simulation modelling process. These adapted tools, simplementation case diagrams and persims, offer strengths appropriate for simulation projects where complex human behaviours must be captured, scaled and represented within the model.